Care for a pet chimpanzee - Leavitt, Amie Jane. (Hockessin, Del. : Mitchell Lane, 2008)
Describes the social behavior of chimpanzees in the wild and explains why making a chimp a pet is a bad idea, discussing the dangers posed to chimpanzees by hunters and the clearing of rain forests.
So, you want a pet chimpanzee? -- Chimps are not monkeys -- One big happy family -- Chimps in danger -- How can I help the chimps? -- Find out more.
Includes bibliographical references (p. 29-30) and index.
2.1
K-3
Keywords: Chimpanzees as pets -- Juvenile literature; Chimpanzees as pets; Chimpanzees; Pets; Chimpanzees as pets; Chimpanzees; Pets